Dokument, fikcja, mit? O kontekstach dramatu Batumi Michaiła Bułhakowa - Fast, Piotr (Przegląd Rusycystyczny, 2011)
ДОКУМЕНТ, ВЫМЫСЕЛ, МИФ? КОНТЕКСТЫ ПЬЕСЫ БАТУМ МИХАИЛА БУЛГАКОВА Резюме В статье представляется биографическая ситуация писателя в конце его жизни и ос-новные общественно-политические и художественные контексты, обуславливающие работу над драмой: пропагандистский миф вождя, народные представления о «хозяи-не», стандарты соцреалистического письма и традиция апокрифической ленинианы. DOCUMENT, FICTION, MYTH?ON THE CONTEXTS OF MIKHAIL BULGAKOV’S BATUM Summary The article presents the biographical situation of Bulgakov in the last years of his life and the major social, political, and artistic consideration bearing on his work on the play centered around Stalin’s youth, such as: the Leader mythos furthered by state propaganda, folk conceptions of the hero of modernity, the artistic and ideological demands of socialist realism and the tradition of apocryphal writings on Lenin.